Reforming Global Criminal Justice: Addressing Corruption’s Impact on Armed Crime - Voloshanivska , Tetiana; Shchokin , Rostyslav; Pavlova , Olena; Frantsuz, Anatoliy Y.; Dei , Maryna O. (Journal of Law and Legal Reform, 2024)
The article examines the relationship between corruption and gun crime and emphasizes the need to counteract this phenomenon to ensure the safety of citizens. The article points to the importance of a proper justice system and reforms in this area to combat corruption and gun-related crimes. The authors of the article analyzed several countries in Africa and Latin America based on corruption and crime rates. The study showed that a high level of corruption directly affects a high level of crime and vice versa. Moreover, the study showed that countries in the same region, with similar stages of development, have different levels of corruption. This suggests that if the recommendations contained in the article are followed, it is possible to overcome corruption and reduce the level of other crimes that are directly related to it. In addition, the authors of the article emphasize the need to modernize and further develop the global strategy of criminal liability for corruption and other crimes arising from it. In general, it should be noted that the importance of international cooperation is extremely high, especially in the context of the international fight against corruption. International cooperation is a key tool in the global fight against corruption and armed crime, as these types of crimes can be international in nature and require coordination of efforts of different countries to be successfully overcome.